A modified LTE simulator for 3D femtocell networks - Zyoud, Al-Hareth; Habaebi, Mohamed Hadi; Islam, Md Rafiqul; Chebil, Jalel; Al-Shibly, Mohammed Abuljawad M; Lwas, Ali Kadhim; Alfaqawi, Mohammed (Asian Research Publishing Network (ARPN), 2016)
Using simulation tools save the construction cost of the wireless system. It is not necessary to establish the system and test whether it is working properly or not. Therefore, simulation tools are required to be accurate, simple and with the minimum time. From the accuracy perspective, the stacked femtocells built in most available simulators in the literature are widely deployed horizontally. However, this is not the case in the indoor environment where femtocells have to be arranged vertically; such as, in residential towers where apartments are on the top of each other. In this paper, the state of the art of link and system level simulators is introduced. In addition, a three-dimensional (3D) system level simulator is developed in order to help the researcher in the Long Term Evolution (LTE) femtocell field to analyze and investigate more real scenarios of femtocell deployment. The developed simulator allows the researcher to locate a multi-story building in the region of interest, choose the number of floors, determine the ceiling height, and allocate the position of the femtocell inside the house.